DIGITAL ETHICS AND MORAL CONSEQUENCES USE OF AI IN FRAUD PREVENTION AND SOCIAL ACCOUNTABILITY IMPACT ON THE TRANSPARENCY FINANCIAL REPORTS - sartono; Darmansyah; Syahril Djaddang; Suratno (Universitas Tulungagung, 2025)
The aims research that digital ethics and the moral consequences of Artificial Intelligence (AI) prevent fraud prevention and social accountability, and their impact on the transparency and sustainability of financial reports in manufacturing companies listed on the Jakarta Stock Exchange. Digital transformation has reshaped accounting and reporting systems, with increasing reliance on AI for transaction processing, risk analysis, and internal monitoring, while raising ethical concerns such as algorithmic bias, data privacy, and moral responsibility. This guides responsible AI use, while moral consequences influence reporting integrity and stakeholder trust. This study employs a quantitative survey of 386 respondents, including financial managers and staff, analyzed using multiple regression and path analysis. The results show that This significantly affects fraud prevention, moral consequences influence social accountability, and both enhance reporting transparency and sustainability. The findings strengthen digital ethics, agency, and stakeholder theories, support ethical AI governance, and increase public trust in financial reporting